Preparing leaders for wicked problems? How the revised PSEL and NELP standards address equity and justice - Amy N. Farley; Joshua Childs; Olivia Johnson (Arizona State University, 2019)
The past 20 years have seen a shift in school leaders' work that can best be characterized by an increasing complexity in expectations and greater demands for accountabilities. Educational leadership preparation programs and professional associations responded to these shifts, in part, with the development and proliferation of standards for both pre-service (ELCC and NELP) and practicing (ISLLC and PSEL) educational leaders. Both sets of standards have undergone significant revision in the last five years, largely in response to shifts in the work required of school administrators in today's 21st century schools. However, what remains an open empirical question is whether the leadership standards are robust and pragmatic enough to tackle the various educational issues that school leaders face. In other words, do various school leadership standards prepare and assess school administrators appropriately? Using the wicked problems framework, we examine the extent to which the revised PSEL and NELP standards capture the challenging work required for school leaders to act as inclusive leaders and "equity-oriented change agents" (Maxwell, Locke, Scheurich, 2013, p. 1). We utilize qualitative content analysis (Weber, 1990) to analyze the content of the leadership standards, focusing in particular on the ways those standards represent evolving conceptions of equity and justice. These analyses suggest that although both sets of standards have changed considerably from their predecessors, they may not go far enough to help leaders determine how to implement the proper administrative authority to solve complex issues. This is particularly true as it relates to the persistent, wicked equity problems facing our schools.